Pedagogical Leadership within the Framework of Human Talent Management: A Comprehensive Approach from the Perspective of Higher Education in Ecuador - Mendoza Velazco, Derling José (2021)
University higher education in recent decades has seen the need to participate in projects that lead to its evolution, transformation and adaptation to the demands of current times. The leading role of the teaching professional is becoming more visible in these changes, which is why it is considered that the recognition of it as a leader is of vital importance to transform reality. The study presented has as a general objective to study teacher leadership in the higher education system of Ecuador considering its leading role in the transformative participation of educational processes.